Model Pertanggungjawaban atas Tindak Pidana Korupsi oleh BUMN sebagai Korporasi: Antara Tanggungjawab Korporasi dan Pengurus - Zul Afiatul Kharisma; Brian Bagus Wiyan Putra; Melasari Nurul Hidayah (Jurnal Hukum Lex Generalis, 2021)
States corporate (BUMN) as actors in economic activities in the national economy based on economic democracy have an important role in realizing public welfare, through capital from the state, either partially (PERSERO) or comprehensively (PERUM). In this implementation, BUMN as one of the subjects of corporations can carry out criminal acts of corruption so that they can cause losses to state finances, also society. The process of accountability to BUMN for the Corruption Crimes has been carried out, there are various weaknesses such as obscurity in the definition of state finances, the disparity of judicial decisions, the inaccuracy of the concept of fines, and so on. So it takes a model of accountability and the right arrangement of BUMN to realize justice in society.